Effects of Using Multiple Hands and Fingers on Haptic Performance in Individuals Who are Blind. (June 2014) - Morash, Valerie S; Pensky, Allison E Connell; Tseng, Steven T W; Miele, Joshua A
In a previous paper we documented that sighted participants complete haptic tasks faster with two hands and multiple fingers, but that these benefits are task specific. The present study investigates whether these effects are the same for participants who are blind. We compared the performance of fourteen blind participants on seven tactile-map tasks using seven finger conditions. As with sighted participants, blind participants performed all tasks faster with multiple fingers. Line-tracing tasks were faster with fingers added to an already in-use hand, and sometimes when added to the second hand. Local and global search tasks were faster with multiple fingers and two hands. Distance comparison tasks were performed faster with multiple fingers, but not two hands. Lastly, moving in a straight line was faster with multiple fingers. These results reinforce our previous finding that the haptic system performs best when it can exploit the independence of multiple fingers. Furthermore, in every instance that an effect was different between sighted and blind participants, the blind participants benefitted more from two hands or multiple fingers than the sighted participants. This indicates that the blind participants have learned, through experience or training, how to best take advantage of multiple fingers during haptic tasks.